To spelling issues in the writings of Vasily Simovych (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article provides the analyses  of Vasily Simovych’s  research of the Ukrainian spelling and  the History of the reform Ukrainian spelling, main directions of research of the Ukrainian spelling.
Keywords: spelling; History of the Ukrainian spelling; Drahomanivka; Kulishivka; Latin